A Simulation of the Biomechanical Behavior of Orthodontic Miniscrews for Infrazygomatic Anchorage: An In Vitro Study - Mario Palone; Davide Tucci; Marta Calza; Niki Arveda; Francesca Cremonini; Filippo Pepe; Luca Lombardo (Sci, 2025)
Background: This study aims to investigate the biomechanical characteristics of orthodontic miniscrews manufactured for use in infrazygomatic crests. Methods: This study analyzed the Zygomatic Spider Screw (HDC, Thiene, Italy), considering four variables: length, insertion angle, insertion depth, support thickness. Twenty-two configurations were tested on 66 miniscrews, all with a diameter of 2 mm, and were inserted into D1 bone-like supports. After compression tests, the deformation angles and linear distances between the tips of the miniscrews were measured. Results: Power analysis showed 99% power for the deformation angles and linear distance. The ICC indicated the good repeatability of the results, with values above 0.70. The mean maximum load values ranged from 21.5 N to 228.8 N, while the mean deformations ranged from 0.45 mm to 2.26 mm. Miniscrews with greater insertion depths (6 and 8 mm) exhibited approximately twice the average deformation (1.5 mm) compared to those inserted at 2 and 4 mm (0.71 mm). It was noted that miniscrews with higher deformation and a lower applied load were those with a working part length of 10 mm and an insertion depth of 2 mm, while those with lower deformation and a better load-bearing capacity were those with a working part length of 6 mm that were fully inserted into the bone support. Conclusions: The miniscrew design and insertion depth significantly affect biomechanical properties. It is advisable to maximize the insertion depth and minimize the distance between the support and the point of force application. The insertion angle did not prove to be a determining factor in the load.